Work accident viewed on counterproductive work behavior: The case study of PT. Pertamina - Suhendri; Suhariadi, Fendy; Herachwati, Nuri; Trisliatanto, Dimas Agung; Puspito, Hendro (Technium Social Sciences Journal, 2024)
Work accidents occurred upstream and downstream company project activities. PT. Pertamina would be one of the causes of disruption or cessation of project work activities. The risk of failure always existed in every work activity, and when a work accident occured, no matter how small, it could result in detrimental effects, therefore as much as possible and as early as possible, potential work accidents must be prevented or at least reduced in their impact. The lack of knowledge about occupational safety and health was largely due to the belief that occupational safety and health programs would be an additional burden on company costs, even though if we took into account the amount of compensation and compensation funds for work accident victims were smaller than the profits. This research aimed to identify and analyze the occurrence of work accidents at PT. Pertamina in terms of counterproductive work behavior. The approach used in this research was a qualitative approach with a case study research design. The results of the research concluded that the adoption of counterproductive work behavior was starting to be widely implemented in the field of occupational safety and health in order to minimize the number of work accidents and prevention of work accidents could be carried out using methods of elimination, substitution, technical engineering, administrative control and the used of personal protective equipment for workers.